Ibn ‘Athiyyah wa Tarjîh fi al-Muḥarrar al-Wajîz - Rochmad Abdurrasyid (Universitas Darussalam Gontor, 2017)
Ibnu Athiyah wrote in his tafsir’s book with very simple language and it’s detailed study and consistency in explaining different styles when explaining. This article reveals, that Ibnu Athiyah used explaining methods, such as explaining with verses of the Qur’an, Hadith, commentary from the companions and tabi'in, explaining with direct al-Qur'an language, siyaq, qirâ'ât, with classical poetry, asbâb an-nuzûl, and Arabic language. That is why his book was held in high esteem by the ulama of the past. From a language perspective, Ibnu Athiiyyah is quite unique, in the fact that he usually utilized classical poetry, thus there are a thousand forms of poetry in Muharrar al-Wajîz book. This is Ibnu Athiiyyah's magnum opus: Muharrar al-Wajîz, he is one of the most phenomenal figures ever produced from the western provinces of the Islamic empire.